2020
DOI: 10.3390/pathogens9090690
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Legiolert Test vs. ISO 11731 to Confirm Legionella pneumophila Contamination in Potable Water Samples

Abstract: Detection and enumeration of Legionella in water samples is of great importance for risk assessment analysis. The plate culture method is the gold standard, but has received several well-known criticisms, which have induced researchers to develop alternative methods. The purpose of this study was to compare Legionella counts obtained by the analysis of potable water samples through the plate culture method and through the IDEXX liquid culture Legiolert method. Legionella plate culture, according to ISO 11731:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…This study confirms results reported from 10 previous studies using Legiolert, indicating this method works as well or better than BCYE‐based methods for recovery and detection of L. pneumophila in water samples: cooling towers (Barrette, 2019); drinking water in distribution systems (LeChevallier, 2019a, 2019b); public bathing water and hot springs (Inoue et al, 2020), potable and nonpotable (Monteiro et al, 2021; Petrisik & Hall, 2018); nonpotable, cooling towers (Rech et al, 2018); building potable and nonpotable (Sartory et al, 2017); potable water (Scaturro et al, 2020); and building potable and nonpotable (Spies et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms results reported from 10 previous studies using Legiolert, indicating this method works as well or better than BCYE‐based methods for recovery and detection of L. pneumophila in water samples: cooling towers (Barrette, 2019); drinking water in distribution systems (LeChevallier, 2019a, 2019b); public bathing water and hot springs (Inoue et al, 2020), potable and nonpotable (Monteiro et al, 2021; Petrisik & Hall, 2018); nonpotable, cooling towers (Rech et al, 2018); building potable and nonpotable (Sartory et al, 2017); potable water (Scaturro et al, 2020); and building potable and nonpotable (Spies et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in recent years on improving the method for culture detection of Legionella in drinking water and the water distribution network [35][36][37]. The Legionella monitoring methods by ISO 11731 and the U.S. CDC also provide a reliable framework for culturing Legionella in drinking water [38,39].…”
Section: Legionella Risk Post Hurricanesmentioning
confidence: 99%
“…In drawing comparisons between the Legionella concentrations, it should be noted that qPCR results may overestimate the viable Legionella. Previous studies concluded that qPCR is useful for rapid detection and risk assessment, but often detect higher amounts than by culture methods, especially from water tanks which have been disinfected [34,35]. On the other hand, Hamilton et al, (2017) [33] noted in a study on seasonality and RHRW premise plumbing pathogens that culture-based methods can underestimate concentrations due to the presence of viable but nonculturable (VBNC) cells.…”
Section: Legionella Risk Post Hurricanesmentioning
confidence: 99%
“…The test detects one L. pneumophila in 100 mL, with results ready in 7 days. Extensive studies have found that the Legiolert assay performed better than conventional methods, with a higher specificity for L. pneumophila in both potable and non-potable water [10][11][12][13][14]. The analytical technique for the Legiolert test is similar to the total coliform Colilert test, so the process is familiar to water utility laboratories [5].…”
Section: Develop L Pneumophila Monitoring Protocolsmentioning
confidence: 99%